Penerapan Metode Economic Order Quantity (EOQ) Pada UD MBO Bakery di Kabupaten Jember - Devi Hikmahwati; Fredy Eka Ardhi Pratama (Politeknik Negeri Jember, 2023)
This research is a type of quantitative descriptive research with the aim of analyzing the optimal amount of wheat flour raw material inventory, safety stock, reoder point, total cost and comparing the company's conventional method of wheat flour raw material inventory control system with the EOQ method. The analytical tools used are the Economic Order Quantity (EOQ) method, order frequency, ROP (reorder point), SS (safety stock), TIC (Total Inventory Cost), and POM-QM software. Based on the results of the analysis, it is known that in 2022 the purchase of UD MBO Bakery raw materials was 139,575 kg with an order quantity of 2,908 kg or 116 bags/order and an order frequency of 50 times/year with an average of 4 times/month and a total inventory cost of IDR 3,919,700.00. Calculations using the EOQ method obtained the optimal amount of raw material purchases in 2022 of 8,063 kg or 322 bags per order with a frequency of purchases of 17 times/year or orders every 18 days and the total cost of inventory using the EOQ method is IDR 2,419,040.81. This shows that calculations using the EOQ method can save total inventory costs of IDR 1,500,659.19.